Konseling Individu dengan Teknik Rational Emotive Behaviour Therapy (REBT) dalam Meningkatkan Kepercayaan Diri (Studi Kasus Klien “A”) - Wahyu Muhamad Noufal; Abdur Razzaq; Zhila Jannati (Journal of Society Counseling, 2023)
The purpose of this research is to determine the description of lack of self-confidence, to determine the process of implementing individual counseling using the Rational Emotive Behavior Therapy technique, to determine the obstacles in individual counseling using the Rational Emotive Behavior Therapy technique. This research uses a qualitative research approach, and the research method used in this research is the case study method. Data collection tools in this research are observation, interviews and documentation. The data analysis techniques in this research are data reduction, data presentation, and conclusions or verification. The subject of this research is client "A" in Lubuk Saung village. The results of this research show that client "A" has low self-confidence, including being unsure of himself, not having confidence in his abilities and competence, not having the courage to accept and face rejection from other people, and unstable emotions, among other symptoms of weakness. Then there are changes in the client, namely being calmer and more patient in responding to things, being able to choose what is good and leaving what is bad for himself, being able to face rejection from other people and being confident in his abilities and knowledge based on his experience and calculations.